Multicomponent Reactions Upon the Known Drug Trimethoprim as a Source of Novel Antimicrobial Agents - Pedrola, Marina; Jorba, Marta; Jardas, Eda; Jardi, Ferran; Ghashghaei, Ouldouz; Viñas, Miguel; Lavilla, Rodolfo (Frontiers in Chemistry, 2019)
Novel antibiotic compounds have been prepared through a selective multicomponent reaction upon the known drug Trimethoprim. The Groebke-Blackburn-Bienaymé reaction involving this -aminoazine, with a range of aldehydes and isocyanides afforded the desired adducts in one step. The analogues display meaningful structural features of the initial drug together with relevant modifications at several points, keeping antibiotic potency and showing satisfactory antimicrobial profile (good activity levels and reduced growth rates), especially against methicillin-resistant Staphylococcus aureus. The new products may open new possibilities to fight bacterial infections.